Keamanan Nasional di Kawasan Asia Tenggara: Analisis Kelembagaan dalam Relasi antara Kepentingan Keamanan Nasional dan UNCLOS - Pratomo, AB (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2020)
The effort by Indonesia to exert their influence in the Southeast Asia region has been motivated by Indonesian leaders to develop a zone where solidarity is possible. The backdrop of post-colonial and Cold War context shaped this exertion into modest aspiration. Indonesia employs ASEAN into various dealings with regional affairs. The achievement of ASEAN has been its step-bystep arrangement which quite conforms its internal contrast of socio-cultural diferences among nation. This worked until the coming of globlisation which bring a various contest of interest, aspiration, and infuence. The proposition of employing UNCLOS in supporting and extending Indonesia’s exertion is not very prominent. However, UNCLOS, in significant part, reflects the history of “Djuanda Declaration”. UNCLOS has potential in covering the width and complexity of the reality of archipelago. The case for UNCLOS is based on revisit into institutional framework of “national security” and the rearticulation of provision of UNCLOS as important part of this framework.